A Comprehensive Review on Physiological Effects of Curcumin - Ahsan, Rabiya; Arshad, Md; Khushtar, Mohammad; Ahmad, Mohd Afroz; Muazzam, Mohammad; Akhter, Md Sohel; Gupta, Gudiya; Muzahid, Mohd (Drug Research, 2020)
Turmeric (Curcuma longa Linn) is an herbal medicine which is traditionally used as a spice, food colouring or flavouring agent and widely used for several diseases such as biliary disorders, cough, hepatic disorders, rheumatism, wound healing, sinusitis, diabetes, cardiac disorders and neurological disorder. It belongs to the Zingiberaceae family. Turmeric is a popular domicile remedy used in Indian food, is mainly a native of south-east Asia, is widely cultivated in India, Sri Lanka, Indonesia, China, Jamaica , Peru, Haiti and Taiwan and it is very less expensive. Curcumin is the main principle of turmeric. Curcumin has shown various biological properties pre-clinically and clinically. Curcumin is a highly pleiotropic molecule which can be modulators of various intracellular signalling pathways that maintain cell growth. It has been reported as anti-inflammatory, anti-angiogenic, antioxidant, wound healing, anti-cancer, anti-Alzheimer and anti-arthritis and possesses an excellent safety profile. All previous review articles on curcumin have collected the biological/pharmacological activities but this review article summarises the most interesting in vitro and in vivo studies of curcumin on most running diseases around the whole world.
Keywords: anti-inflammatory drugs; cardiovascular pharmacology; pharmacology; pulmonary & respiratory pharmacology; inflammation; cardiovascular diseases